Sandwich Results for Multivalent Analytic Functions Associated with Borel Distribution and Ruscheweyh Derivative - Ghali, Zainab Swayeh; Wanas, Abbas Kareem (Iraqi Journal of Science, 2025)
In this work, we obtain some differential subordination and superordination results defined by Hadamard product for multivalent analytic functions with Borel distribution and Ruscheweyh derivative in the open unit disk. We applied these results and obtain sandwich results.